1998
DOI: 10.1016/s0735-1097(98)00002-3
|View full text |Cite
|
Sign up to set email alerts
|

Peak Exercise Oxygen Consumption in Chronic Heart Failure: Toward Efficient Use in the Individual Patient

Abstract: A contraindication to exercise testing should be considered a priority for listing patients for heart transplantation. Only in less symptomatic male patients does a peak VO2 < or = 10 ml/kg per min identify short-, medium- and long-term high risk groups. A peak VO2 >18 ml/kg per min implies good prognosis with medical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
84
3
5

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(98 citation statements)
references
References 31 publications
5
84
3
5
Order By: Relevance
“…In moderate and severe CHF, peak V O 2 constitutes an integral part of patients' pretransplant assessment, with some various cutoff values having been proposed for decision-making. [2][3][4]13 The prognostic strength of peak V O 2 measurements, however, lies predominantly in patients with advanced symptoms and at least moderate functional impairment, as previously known from several studies 1,3,4 and confirmed by our supplementary analysis of patients with less-well-preserved exercise tolerance. Yet data from large trials show that death is not rare in patients with mild symptoms: annual mortality ranges from 8% to 10%, and sudden death is not uncommon.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…In moderate and severe CHF, peak V O 2 constitutes an integral part of patients' pretransplant assessment, with some various cutoff values having been proposed for decision-making. [2][3][4]13 The prognostic strength of peak V O 2 measurements, however, lies predominantly in patients with advanced symptoms and at least moderate functional impairment, as previously known from several studies 1,3,4 and confirmed by our supplementary analysis of patients with less-well-preserved exercise tolerance. Yet data from large trials show that death is not rare in patients with mild symptoms: annual mortality ranges from 8% to 10%, and sudden death is not uncommon.…”
Section: Discussionsupporting
confidence: 80%
“…3,4 Considering NYHA functional classification as being fairly subjective, we decided to use peak V O 2 as an objective measure of exercise capacity for selection of our patients. It has been demonstrated that peak V O 2 values Ն18 mL · kg Ϫ1 · min Ϫ1 identify CHF patients who have only mildly impaired or nearly normal exercise capacity and are considered to imply uniformly good outcome.…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have showed that peak oxygen uptake (VO 2 ) obtained at maximal exercise provides not only an objective measure of functional capacity, but also prognostic information in patients with CHF. [9][10][11][12][13][14] We predict that patients with exercise intolerance are those with higher neurohormonal and cytokine activation, however, the relation between peak VO 2 and multiple neurohormone/cytokine levels has not been clearly elucidated. Thus, we conducted the present study to clarify the relation between neurohormonal/cytokine activation and functional capacity as measured by cardiopulmonary exercise testing in patients with mild to moderate CHF.…”
mentioning
confidence: 99%